Least Risky Change Propagation Path Analysis in Product Design Process. Issue 4 (29th August 2017) - Ullah, Inayat; Tang, Dunbing; Wang, Qi; Yin, Leilei
ABSTRACT: Requirement changes play a significant role in the product design and development process and constantly change due to the customers' expectations. This research seeks to develop an advanced approach for the product designing with an aim to predict the least risky change propagation path (CPP) in the product's structure. This is achieved by developing an algorithm and a mathematical model taking the overall propagated risk into consideration. The risks associated with requirement changes, which would result in rework, are quantified in terms of propagation probability and change impact. The proposed algorithm relates the change risk to the amount of rework needed to be done. The outcomes indicate the suitability of the proposed method in assessing different least risky CPPs to support the designer in reducing redesign time. Moreover, this technique also provides additional information, such as the number of distinct design components, and change steps involved in change propagation. A case study is presented to demonstrate the practicability of the proposed technique.